Improved synthesis of 4-cyanotryptophan and other tryptophan analogs in aqueous solvent using variants of TrpB from Thermotoga maritima - Boville, Christina E. (J Org Chem, 2018)
The use of enzymes has become increasingly widespread in synthesis as chemists strive to reduce their reliance on organic solvents in favor of more environmentally benign aqueous media. With this in mind, we previously endeavored to engineer the tryptophan synthase β-subunit (TrpB) for production of noncanonical amino acids that had previously been synthesized through multistep routes involving water-sensitive reagents. This enzymatic platform proved effective for the synthesis of analogs of the amino acid tryptophan (Trp), which are frequently used in pharmaceutical synthesis as well as chemical biology. However, certain valuable compounds, such as the blue fluorescent amino acid 4-cyanotryptophan (4-CN-Trp), could only be made in low yield, even at elevated temperature (75°C). Here, we describe the engineering of TrpB from Thermotoga maritima that improved synthesis of 4-CN-Trp from 24% to 78% yield. Remarkably, although the final enzyme maintains high thermostability (T(50) = 93°C), its temperature profile is shifted, such that high reactivity is observed at ~37°C (76% yield), creating the possibility for in vivo 4-CN-Trp production. The improvements are not specific to 4-CN-Trp; a boost in activity at lower temperature is also demonstrated for other Trp analogs.